Low dose DTIC is effective and safe in pretreated patients with well differentiated neuroendocrine tumors. Issue 1 (December 2016) - Mueller, Daniela; Krug, Sebastian; Majumder, Moushumee; Rinke, Anja; Gress, Thomas
Abstract Background Streptozocin (STZ) based chemotherapy is recommended for patients with metastatic pancreatic neuroendocrine tumors (pNET). Temozolomide as mono- or combination therapy has been suggested to be a promising alternative. However, the treatment is costly and not approved for the treatment of pNETs. Dacarbazine (DTIC) shares the active metabolite with temozolomide and is broadly available at a low cost. The aim of this study was a retrospective evaluation of the efficacy and tolerability of a lower dose DTIC-regimen in patients with progressive advanced NETs. Methods We retrospectively analyzed 75 patients with NETs predominantly of pancreatic origin treated at our center between 1998 and 2013. 650 mg/m2 of DTIC were administered intravenously over 60 min every 4 weeks. Morphological response was assessed according to RECIST1.1 criteria. The median progression free survival (PFS) was calculated using Kaplan-Meier and Cox regression methods, respectively. Univariate analyses of possible prognostic markers were performed. Results The objective response rate (ORR) was 27 % for the entire cohort and 32 % in 50 pNET patients, respectively. Stable disease (SD) was documented in 29 patients (39 %). Median PFS (mPFS) in patients receiving DTIC was 7 months (3.9–10; 95 % confidence interval). Radiological and biochemical response were the only significant prognostic markers for longer PFS in univariate analysis. Treatment was well tolerated. Nausea was the most common side effect (31 %), only one case (1.3 %) of grade 3 toxicity (vomiting) occurred. Conclusion Low dose DTIC chemotherapy is an effective and well-tolerated treatment option in patients with progressive well differentiated neuroendocrine neoplasms, especially of pancreatic origin.